Dampak Poligami Terhadap Perkembangan Anak - Buhari, Daudy; Harahap, Efrida Wati; Endayana, Bestari (Yayasan Literasi Kita Indonesia, 2024)
Polygamy is a marital practice of marriage in which a man has more than one wife simultaneously. In this context, the impact of polygamy one child development becomes a significant concern. Research has shoown that polygamy can have comlex and varied effects on child development. In this abstract, we will discuss some of the main impacts of polygamy on child development, including emotional, social, and psychological effects. In terms of emotional impact, children in polygamous families may strugglle to undrstand and manage their feelings related to the complex family situation. They may feel jealous, insecure, or neglected due to the divided attention and time between multiple mothers and siblings. This can lead to prolonged emotional stress and affect their mental well-being. The social impact of polygami on children also needs to be considered. In polygamous families,children have half-siblingsfrom diffrent mothers. This dynamic can create comlexity in sibling relationships and affect family bonds. Children may strugglle to build strong and supportive relationships with their half-siblings, especially if there is competition or perceived unfairness within the family. Additionally, children in polygamy may also face social stigma and difficulties in interacting with their peers outside the family environment. The psycologicalimpact of polygamy on child development is also important to consider. Children in polygamous families may experience identity conflicts and difficulties in understanding their roles within the complex family structure. They may find challenging to meet the expactations and demands placed upon them by multiple mothers and fathers. This can affect their identity development and increase the risk of psychological issues such as anxiety, deppression, or low selff-esteem.